Schooling in Western Europe - Jones, K. author. aut Link
VIII, 225 p.
Keywords: Schooling in Europe is being transformed by a new policy orthodoxy affecting all aspects of the school. Privatization, decentralization, and business focused curriculum reform are all on the rise. The authors consider the impact and conflict of such changes on schooling in England, France, Germany, Italy and Spain.